2015
DOI: 10.17784/mtprehabjournal.2015.13.329
|View full text |Cite
|
Sign up to set email alerts
|

The trunk extensor flexor relationship in men and women by isokinetic dynamometry

Abstract: Introduction:The thoracolumbar musculature plays a key role in the balance and stability of the pelvis. The isokinetic dynamometer provides accurate assessment of muscle performance and treatment guidance. Objective: To compare the flexors / extensors of the trunk link between sedentary men and women, asymptomatic by isokinetic dynamometry. Method: An observational cross-sectional study. The sample consisted of 100 asymptomatic sedentary volunteers, 50 males and 50 females with a mean age of 22.2 ± 3.3 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Our values seem to be smaller than of literature (64% to 72% without gravity correction, according to the authors, or 80% to 85% with gravity correction) ( Bernard et al, 2014 ). Simlarly, Simbala et al (2015) assessed a group of asymptomatic sedentary individuals, and reported a ratio of the peak torque of the flexors to the extensors of 81% for males. In our study, the ratio of the peak torque of the flexors to the extensors in the athletes group was smaller than in the nonathletes group.…”
Section: Discussionmentioning
confidence: 99%
“…Our values seem to be smaller than of literature (64% to 72% without gravity correction, according to the authors, or 80% to 85% with gravity correction) ( Bernard et al, 2014 ). Simlarly, Simbala et al (2015) assessed a group of asymptomatic sedentary individuals, and reported a ratio of the peak torque of the flexors to the extensors of 81% for males. In our study, the ratio of the peak torque of the flexors to the extensors in the athletes group was smaller than in the nonathletes group.…”
Section: Discussionmentioning
confidence: 99%